IMPLEMENTASI PEREKAMAN E-KTP DI KABUPATEN CIANJUR PROVINSI JAWA BARAT (STUDI KASUS DI KECAMATAN CIRANJANG) - Bertha Lubis; S. Mulyaningsih (Jurnal Ilmiah Wahana Bhakti Praja, 2016)
AbstractResearch intention to obtain an overview of e-ID card policy implementation in the DistrictCiranjang Cianjur. Objective 1) To determine and analyze the coordination between theDepartment of Population and Civil Registration with the District and 2) To determine theconstraints in the implementation of e-ID card in District Ciranjang Cianjur.This study used a descriptive research design analysis with a qualitative approach. This studyincludes qualitative research, which produces descriptive data. Qualitative research is alsomore emphasis on the process rather than in terms of results, but that with this research mayreveal the problem of what is in accordance with the reality on the ground. Scope of thisresearch is on the implementation of e-ID card policy.The primary data source is interviews with sources (informants) and take into account anyinformant, supported by secondary data from document texts, written data, and photographs.Data Collection Techniques and Instrument Research Interview/Interview and DocumentationData analysis technique used in this study is the analysis by collecting interactive model.Analysis of data: reduction, data display and conclusion Withdrawal.Keywords: population, recording and e-ID card